Diet-Induced Weight Loss Reduces DNA Damage and Cardiometabolic Risk Factors in Overweight/Obese Women with Polycystic Ovary Syndrome - Soares, Nayara Pereira; Souza dos Santos, Ana Celly; Costa, Eduardo Caldas; Azevedo, George Dantas; Damasceno, Débora Cristina [UNESP]; Trussardi Fayh, Ana Paula; Araujo Moura Lemos, Telma Maria (Karger, 2016)
Aims: We aimed to investigate the impact of following a diet to induce weight loss (500 kcal deficit per day) over DNA damage and cardiometabolic risk factors in women with overweight/obesity diagnosed with polycystic ovary syndrome (PCOS). Methods: A study was conducted in Natal, RN, Brazil selecting overweight/obese (body mass index >= 25 and <39 kg/m(2)) women (18-35 years). The levels of DNA damage were assessed by a single cell gel electrophoresis. Repeated 24 h dietary recall questionnaires, anthropometry, biochemical profile and sex hormones were collected at baseline and after 12 weeks of intervention. Results: Women exhibiting a decrease in the markers of DNA damage: tail intensity (24.35 +/- 5.86 - pre diet vs. 17.15 +/- 5.04 - post-diet; p < 0.001) and tail moment (20.47 +/- 7.85 - pre diet vs. 14.13 +/- 6.29 - post-diet; p < 0.002). Reduction of calorie intake, weight loss, decreased sexual hormone and cardiometabolic markers such as insulin, homeostasis model assessment of insulin resistance and low-density lipoprotein cholesterol were verified In the multivariate regression analysis, quantitative insulin sensitivity check index and progesterone were responsible for the variation markers in DNA damage before the diet, losing its influence upon diet. Conclusion: DNA damage and the impact of cardiometabolic risk factors decreased after the intervention in women with PCOS, indicating the relevance of a nutritional approach in this group of patients. (C) 2016 S. Karger AG, Basel
Keywords: Diet; DNA damage; Cardiometabolic risk factors; Overweight; Obesity; Polycystic ovary syndrome